Measuring urban design : metrics for livable places - Ewing, Reid (Metropolitan Planning + Design, 2013)
What makes strolling down a particular street enjoyable? The authors of Measuring Urban Design argue it's not an idle question. Inviting streets are the centerpiece of thriving, sustainable communities, but it can be difficult to pinpoint the precise design elements that make an area appealing. This accessible guide removes the mystery, providing clear methods to measure urban design.   In recent years, many "walking audit instruments" have been developed to measure qualities like building height, block length, and sidewalk width. But while easily quantifiable, these physical features do not fully capture the experience of walking down a street. In contrast, this book addresses broad perceptions of street environments. It provides operational definitions and measurement protocols of five intangible qualities of urban design, specifically imageability, visual enclosure, human scale, transparency, and complexity.   The result is a reliable field survey instrument grounded in constructs from architecture, urban design, and planning. Readers will also find a case study applying the instrument to 588 streets  in New York City, which shows that it can be used effectively to measure the built environment's impact on social, psychological, and physical well-being. Finally, readers will find illustrated, step-by-step instructions to use the instrument and a scoring sheet for easy calculation of urban design quality scores.   For the first time, researchers, designers, planners, and lay people have an empirically tested tool to measure those elusive qualities that make us want to take a stroll. Urban policymakers and planners as well as students in urban policy, design, and environmental health will find the tools and methods in Measuring Urban Design especially useful.